The Role and Impact of Artificial Intelligence on Public Sector Audit Transformation in the Digital Era - Kau, Sasmita Trimoelya; Fitriana, Fitriana (E-Jurnal Akuntansi, 2025)
Amidst the data revolution and digital transformation, implementing artificial intelligence (AI) in public sector auditing is increasingly relevant, offering potential for enhanced efficiency. Addressing prior research limitations, notably the lack of systematic reviews and restricted ethical focus, this study investigates the factors driving AI adoption and their interrelations within this specific context. Adopting a systematic literature review (SLR) approach based on PRISMA and de Bakker et al. (2019), 73 pertinent articles from the Scopus database (2019-2024), identified via specific keywords, were comprehensively analyzed using NVivo for thematic classification. Key findings reveal diverse AI roles, including transforming audit reporting and enabling continuous auditing/monitoring. The study underscores the urgent need for developing adaptive auditor competencies and addresses accompanying ethical challenges. Ultimately, this research provides a deeper understanding of AI's opportunities and challenges, contributing valuable insights for developing more adaptive and technologically responsive public sector audit practices. Keywords: Artificial Intelligence (AI); Public Sector Auditing; Continuous Auditing; Digital Transformation; Audit Ethics.